Respuesta :

Answer:

(x-9)(x-3) which is the same as (x-3)(x-9)

Step-by-step explanation:

Think of ways to factor the last number 27. One way is 1*27 = 27. Another way is 3*9 = 27 and so on. Now think to yourself "which factor of 27 add to -12?". You'll need to consider negative factors. It turns out that

-3 plus -9 = -12

-3 times -9 = 27

Therefore the two values we care about are -9 and -3. So x^2-12+27 factors to (x-3)(x-9). The order of the factors does not matter. So we can write the answer as (x-9)(x-3) just fine.